Astaxanthin alleviates renal damage of rats on high fructose diet through modulating NFκB/SIRT1 pathway and mitigating oxidative stress. (1st January 2020) - Iskender, Hatice; Yenice, Guler; Dokumacioglu, Eda; Hayirli, Armagan; Sevim, Cigdem; Dokumacioglu, Ali; Terim Kapakin, Kubra Asena
Abstract: This study was conducted to determine the effect of astaxanthin (ASX) treatment on alleviation of renal damage in high fructose induced nephrotoxicity in rats. Treatments were arranged in a 2 × 2 factorial fashion: administrations of fructose (30%, via drinking water) and ASX (1 mg/kg/day, within 0.2 ml olive oil) for 8 weeks. Data were analyzed by two-way ANOVA. The ASX treatment decreased serum urea ( p < .01) and blood urea–N concentrations ( p < .02) at a lower extent in rats receiving fructose than those not receiving fructose. Moreover, the ASX treatment reversed the increases in malondialdehyde (MDA) ( p < .0001) and nuclear factor kappa B (NF-κB) ( p < .0003) levels and the decreases in superoxide dismutase (SOD) activity ( p < .0001) and sirtuin-1 (SIRT1) level ( p < .0004), in the kidney upon high fructose consumption. The data suggest that ASX supplementation alleviates renal damage induced by high fructose consumption through modulating NF-κB/SIRT1 pathway and mitigating oxidative stress.